Gender Evaluation of Maize Leaf Stripping Practices in Northern Ghana - International Institute of Tropical Agriculture (International Food Policy Research Institute, 2021)
Through research and scaling, Africa RISING strives to create opportunities for smallholder farm households to move out of hunger and poverty. However, knowledge about gendered differences in the adoption of intensification practices is still limited and often based on results from quantitative studies only. The evaluation is to gain an in-depth understanding of gender issues surrounding the adoption and sustainability of maize leaf stripping technologies on the household as well as community level. This includes an understanding of intra-household decision-making and labor allocation; access to resources, participation as well as benefit-sharing among male and female households and community members. The data covers basic demographic information, general farm system description, gender and household processes, and market participation of 60 farmers involved in maize leaf stripping in Northern Ghana. The main data generation strategy of this study was focus group discussions.